A survey of enteric organisms detected by real‐time PCR assay in faeces of dogs in Western Australia. Issue 10 (28th June 2021) - Kim, MW; Sharp, CR; Boyd, CJ; Twomey, LN
Abstract : This retrospective observational study reports the enteric organisms detected in dogs in Western Australia that had a faecal PCR (fPCR) submitted to a commercial veterinary laboratory. Of 2025 fPCR results, Clostridium perfringens alpha toxin gene was most frequently detected (87.2%), followed by Campylobacter spp. (37.8%), canine parvovirus (10.5%), Giardia spp. (9.7%), Salmonella spp. (7.0%), canine enteric coronavirus (2.3%), and canine distemper virus (0.3%). C.perfringens alpha toxin gene and Campylobacter spp. were the most common organisms co‐detected. There was no statistically significant seasonal variation. Further studies are required to elucidate the role these organisms play in gastrointestinal disease in dogs.